Synthesis and characterization of cerium carbonate. (4th August 2014) - Lucchini, E.; Schmid, C .
Sinter–reactive powders of cerium dioxide (ceria) can be effectively prepared by the decomposition of its carbonates. In this paper, three different routes to Ce–carbonate precipitation are described and discussed. Among the use of ammonium carbonate, carbon dioxide and urea, this latter effectively leads to the quantitative precipitation of Ce(+3) basic carbonate compounds. Their thermal decomposition provides tine ceria powders suitable for ceramic purposes.